(untitled) (Global Journal of Management and Business Research, 2014)
Purpose: To become a successful front office professional, a person needs to be comfortable with interacting with strangers and dealing with various hotel-guests issues. To do so effectively, a front office manager needs to understand and apply appropriate findings of psychology. Personality psychology is a branch of psychology that studies personality and individual differences. For years, practitioners of applied psychology have tried to help companies identify personality types of customers and teach them how to handle each of these. By understanding the personality styles of guests, front office managers can easily accommodate the needs of each type. This conceptual paper analyses some of the findings of personality psychology which have direct implications for front office managers and professionals.